STRATEGI PEMASARAN TOKO KOSMETIK DALAM MENINGKATKAN MINAT PELANGGAN DI DAERAH TUASAN KOTA MEDAN SUMATRA UTARA (STUDI KASUS: TOKO LOLIPOP) - Zainarti Zainarti; Anisah Cyntia Dewi Pratama; Abdul rahmad rayadi; Naylatussalwa Makarim (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
Abstract: This research aims to fill this knowledge gap by developing an appropriate marketing strategy for Lollipop Shops in the Tuasan area, Medan City, North Sumatra. The methods that will be used include a segmentation, targeting and positioning (STP) approach, effective digital marketing, appropriate promotions, and developing customer relationships to significantly increase customer interest and loyalty. This research will use a qualitative approach with a case study method to understand the marketing strategy implemented by the Lollipop Shop, customer perceptions and behavior, as well as factors that influence customer interest and loyalty. This approach was chosen because it allows an in-depth analysis of the phenomenon under study. Based on the research results, the marketing strategy implemented by the Lolipop Shop has provided positive results in attracting and retaining customers in the Tuasan area, Medan City. However, there are still several aspects that need to be improved in order to increase customer interest and loyalty and strengthen the store's position in the local cosmetics market.